THE EFFECT OF USING VOA (VOICE OF AMERICAN) NEWS VIDEO ON IMPROVING THE STUDENTS TRANSACIONAL SPEAKING AT SENIOR HIGH SCHOOL SOPPENG - Nawir, Muhammad Syahruddin (English Language, Linguistics, and Culture International Journal, 2022)
Nowadays, there are a lot of online learning platforms. New technologies developed to make learning process easier. One of the examples of online learning platforms is VOA (Voice of American) News. The research aimed to measure the effect of VOA News toward the students’ transactional speaking at Gandra Islamic School Soppeng. This research employed an experiment exactly quasi-experimental research, where the data obtained from the pre-test and post-test. The subjects of this research were 31 students which divided into two groups such as control group which consist of 15 students and experiment group which consist of 15 students at Ganra Islamic School Soppeng. The data was analyzed by using SPSS and found that the H1 was accepted. It proved that the implementation of VOA News improved students’ speaking skill because there was an improvement score from the pre-test to post-test. Based on the finding and discussion of the research, the researcher proposed to provided recommendation especially for an English teacher of Ganra Islamic School Soppeng to imply VOA News as a technique to improve students’ speaking skill.